Sistem Pembelajaran Ujian Nasional untuk Sekolah Menengah Atas Berbasis Website - Kurniadi Prasetia; Arie Kusumawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
E-learning is a solution that exists today to overcome various problems faced by students when there are many problems that arise, such as limited time, place of learning, and also meetings with teachers. For this reason, an E-learning was built using the programming language PHP and MySQL using the Prototype method. The result is that learning is now available in the form of a National Examination for High School learning media. There are 3 actors in this e-learning, namely admin, teacher and students. The results obtained are all users can use this learning website and increase interaction between teacher and student.